ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA - Istiani, Ana; Widiyanto, Hendri; Suningsih, Ari (JURNAL e-DuMath, 2019)
The purpose of this study was to describe the level of students' written mathematical communication skills in solving story problems in algebraic material. The population used is class VIII SMP N 1 Gadingrejo 2017/2018 Academic Year. While the sample is class VIII.9 students with sampling techniques using purposive sampling. The analysis results obtained by students who take the test of written mathematical communication skills there are 11.76% of students who have very low mathematical communication skills, 26.47% of students who have low mathematical communication skills, 38.24% of students who have moderate mathematical communication skills, and 23.53% of students who have high mathematical communication skillsKey Word : Komunikasi matematik, soal cerita, aljabar